Processo de intervenção para a prática integrada de profissionais de saúde no atendimento à criança vítima de violência - Klippel, Yara Aparecida Martini (2013)
The mainpurpose of this present dissertation is to discuss about the actions of the health professionals when they assist young children victims of violence. This research has the purpose of clarifying the problems in between health professionals and young children victims of violence. Therefore, it was chosen a Children´s Hospital, a medium complexity hospital located in Ponta Grossa, Southern Brazil. This type of research started a discussion group about the assistance of young children victims of violence and about the problematic situations faced by the health professionals in a process of action-reflection-action-reflection, considering the ideological, psychological and cultural relation practice that interferes in the attendance practice by these professionals. It was chosen for this work the action-research methodology, because we understand that the psychosocial intervention belongs to a local team, who is the most interested part in building new ways to understand this event. It was used a semi-structured survey as a tool to collect all the data information in order to understand the phenomenon. After this survey, it was scheduled six meetings to discuss the over-interventionist actions performed by the health professionals during their work hours when they faced themselves with children victims of violence complex experiences. This methodology contributed to comprehend the reality inside these professionals daily life, about what´s the real problem and the difficulty behind their daily life. Having the violence against young children as a real problem, a public health problem, it was found some great answers inside these group studies. We have as a result of this research, these following topics: a) recognition of ahigher difficulty in dealing with the young children victims of violence by the health professionals involved; b) the necessity of professional trainings to develop more skills to do a better work; c) the necessity of an assistance protocol to these young children; d) the lack of high qualified professionals to solve the demand; e) the necessity of a better and modern structure inside the hospital that can assist to this higher demand; f) a better service in terms of organization and an inclusion of a flowchart to standardize the procedures and teamwork. The theoretical support to understand this present dissertation is based in authors and laws who treat every child as a subject of rights, respecting the human rights, and the authors who respect the communitarian psychology regarding the strengthening of the health professionals to establish an integrated practice. It is expected a great contribution by this intervention, in showing new possibilities to improve the practice skills by the health professionals to a better assistance of all children victims of violence.